Analysis of the relationship between financial markets and investment: A survey study of the opinions of a sample of investors in the city of Sulaymaniyah - Sazan Aladdin Omar; Kawa Muhammad Faraj Al-Qardaghi (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The current research seeks to analyze relationship between the financial market and investment, from the perspective of investors in Sulamani city. The two researchers used both descriptive and analytical methods in the research which covered the time span between the years (2013- 2018). The questionnaire form was used as a basic tool for the data collection from investors. The research population was representing by investors in Sulaimani Governorate and they were (33) investors. A total of (32) questionnaire were distributed to investors in Sulaimani Governorate from which (30) valid questionnaires were retrieved for analysis. It was tested statistically using (SPSS V.21). Finally, the researchers reached to a set of conclusions, the most important of which is the existence of a significant correlation between the financial market and investment. Based on the conclusions, the research has reached a number of recommendations, the most important of which is the need to pay attention to financial markets as they are an important factor in financing investment projects.